SMARTPHONE PULSE OXIMETER: SOLUSI DETEKSI DINI HAPPY HYPOXIA: SOLUSI DETEKSI DINI HAPPY HYPOXIA - Fachri Naufal; Alfiani Zukhruful Fitri Rifa'i (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2021)
Background: Coronavirus disease 2019 (COVID-19) is a global crisis throughout 2020. Furthermore, COVID-19 is also a challenge due to the phenomenon it can cause: happy hypoxia, where patients came with low oxygen saturation but shows no respiration symptoms and no dyspnea. Discussion: Hypotheses about what causes happy hypoxia emerges, trying to explain how happy hypoxia happened, which defies the pathogenesis theory of COVID-19. Because patients does not experience any infection symptoms, early detection is required to get medical attention as soon as possible. Now, smartphones has oxymeter built in and capable to detect happy hypoxia. Conclusion: Smartphone pulse oxymeter is an effective solution because of it’s portability and easy usage so it can be used for early detection of decreasing oxygen saturation. Patients may get help promptly, and COVID-19 mortality rate will decline.